Governance and social media in African countries: An empirical investigation. (June 2019) - Asongu, Simplice A.; Odhiambo, Nicholas M.
Abstract: This study assesses linkages between social media and governance dynamics in 49 African countries for the year 2012. The empirical evidence is based on ordinary least squares and quantile regressions. Ten bundled and unbundled governance dynamics are used, notably: (i) political governance (entailing "voice & accountability" and political stability/no violence); (ii) economic governance (involving regulation quality and government effectiveness); (iii) institutional governance (comprising the rule of law and corruption-control) and (iv) general governance (entailing political, economic and institutional governance). Social media is measured with Facebook penetration. The findings show that Facebook penetration is positively associated with governance dynamics and these positive nexuses differ in terms of significance and magnitude of significance throughout the conditional distribution of the governance dynamics. Highlights: This study assesses linkages between social media and governance in Africa. The empirical evidence is based on quantile regressions. The findings show that Facebook penetration is positively associated with governance. The nexus is contingent on initial levels of governance.